Comprehensive analyses of core–shell InGaN/GaN single nanowire photodiodes. (6th November 2017) - Zhang, H; Guan, N; Piazza, V; Kapoor, A; Bougerol, C; Julien, F H; Babichev, A V; Cavassilas, N; Bescond, M; Michelini, F; Foldyna, M; Gautier, E; et al.
Abstract: Single nitride nanowire core/shell n-p photodetectors are fabricated and analyzed. Nanowires consisting of an n-doped GaN stem, a radial InGaN/GaN multiple quantum well system and a p-doped GaN external shell were grown by catalyst-free metal–organic vapour phase epitaxy on sapphire substrates. Single nanowires were dispersed and the core and the shell regions were contacted with a metal and an ITO deposition, respectively, defined using electron beam lithography. The single wire photodiodes present a response in the visible to UV spectral range under zero external bias. The detector operation speed has been analyzed under different bias conditions. Under zero bias, the −3 dB cut-off frequency is 200 Hz for small light modulations. The current generation was modeled using non-equilibrium Green function formalism, which evidenced the importance of phonon scattering for carrier extraction from the quantum wells.